ACTIVITIES ON DPPH FREE RADICAL SCAVENGING AND ANTIOXIDANT ENZYMES FROM THE FRUITS OF BITTER GOURD (MOMORDICA CHARANTIA L.) ACCORDING TO CULTIVARS - Ock, H. Boo; Hwa, L. H.; Won, J. Lee; Jin, S. Hwang (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In the Asian sub-continent bitter gourd is extensively used as food and is popular in herbal medicine. This study was carried out in order to determine the biological activities such as antioxidant activities in eight bitter gourd cultivars (Korea, China, Japan and Philippine native cultivars). Free radical scavenging activities of various cultivars of bitter gourd were the strongest in Korea native bitter gourd as RC50 102.6 ug/ml. And its activity was similar to synthetic antioxidant BHT as RC50 95.6 ug/ml. The activity of SOD and CAT were higher in Korea and Japan bitter gourds than Philippine bitter gourd. Activation of APX activity according to cultivars were significantly increased in Korea native bitter gourd (7.82 U/mg protein), Japan cultivar “Nikko” (8.55 U/mg protein), and Philippine cultivar “Galaxy” (8.17 U/mg protein). Antioxidative enzyme activities were increased in the order of SOD > APX > CAT. These results suggest that the bitter gourd had the potent biological activities, and that their activities exhibited differently depending on cultivars.